Heterogeneous Blood-Tumor Barrier Permeability Determines Drug Efficacy in Experimental Brain Metastases of Breast Cancer - Lockman, Paul R. (2010)
PURPOSE: Brain metastases of breast cancer appear to be increasing in incidence, confer significant morbidity, and threaten to compromise gains made in systemic chemotherapy. The blood-tumor barrier (BTB) is compromised in many brain metastases, however, the extent to which this influences chemotherapeutic delivery and efficacy is unknown. Herein, we answer this question by measuring BTB passive integrity, chemotherapeutic drug uptake, and anticancer efficacy in vivo in two breast cancer models that metastasize preferentially to brain. EXPERIMENTAL DESIGN: Experimental brain metastasis drug uptake and BTB permeability were simultaneously measured using novel fluorescent and phosphorescent imaging techniques in immune compromised mice. Drug-induced apoptosis and vascular characteristics were assessed using immunofluorescent microscopy. RESULTS: Analysis of >2000 brain metastases from two models (human 231-BR-Her2 and murine 4T1-BR5) demonstrated partial BTB permeability compromise in >89% lesions, varying in magnitude within and between metastases. Brain metastasis uptake of (14)C- paclitaxel and (14)C- doxorubicin was generally greater than normal brain but <15% of that of other tissues or peripheral metastases, and only reached cytotoxic concentrations in a small subset (~10%) of the most permeable metastases. Neither drug significantly decreased the experimental brain metastatic ability of 231-BR-Her2 tumor cells. BTB permeability was associated with vascular remodeling and correlated with over expression of the pericyte protein, desmin. CONCLUSIONS: This work demonstrates that the BTB remains a significant impediment to standard chemotherapeutic delivery and efficacy in experimental brain metastases of breast cancer. New brain permeable drugs will be needed. Evidence is presented for vascular remodeling in BTB permeability alterations.